PENINGKATAN PROSES DAN HASIL BELAJAR IPA MENGGUNAKAN MODEL KOOPERATIF SNOWBALL THROWING DI SEKOLAH DASAR - Tri Wiyoko; Aprina Detika (LP3M STKIP Muhammadiyah Muara Bungo, 2021)
This research is motivated by the low process and learning outcomes of elementary school students in grade IV SD Negeri No. 002/XI Pasar Sungai Penuh. So it is necessary to do research with the aim of improving the process and learning outcomes of science after using the cooperative model of the snowball throwing type. The research was carried out using classroom action research (CAR) which consisted of two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and evaluation. The subject of this research is the fourth grade students of SD Negeri No. 002/XI Pasar Sungai Penuh as many as 28 people. Data collection instruments in the form of observation sheets and learning outcomes test questions. Analysis of the data used is descriptive qualitative analysis method. The results showed that (1) an increase in the learning process carried out by teachers from the first cycle reached 83% and an increase in the second cycle reached 94.04%. In addition, the student learning process also experienced a very good increase, where in the first cycle it reached 71.4% and increased in the second cycle it reached 89.3%. (2) there is an increase in students' science learning outcomes with the achievement of learning outcomes test scores in the first cycle reaching 76.6% and experiencing a very good increase in the second cycle reaching 88.6%. Thus, the use of the cooperative model of the snowball throwing type can improve the process and learning outcomes of fourth grade science students.